Lima Barreto: representações políticas e culturais dos equilibristas da corda bamba da vida - Rita de Cássia Guimarães Melo (Porto das Letras, 2016)
This article analyzes some characters created by Lima Barreto's novel Recordações do escrivão Isaías Caminha. Between history and literature, we shall state the way the narrative from the historiography of the period elucidates the atmosphere of literary production of the writer. We emphasize the characters that we think represent the median and peripheral groups that inhabited the city of Rio de Janeiro in the early decades of the nineteenth century.